Espia lá : um aplicativo educacional em dispositivo móvel que organiza e facilita o acesso a produtos educacionais - Daron, Érika Cassia de Almeida Soares Kurpel (2015)
Espia lá is an APP that organizes and facilitates the access to educational products, a product that was developed in the Professional Masters in Natural Science of Federal University of Mato Grosso. The first version of the app has 24 of 26 educational products from the Database of Educational Products from the Master's Program of the period between 2012 to 2015. In this way leading these products to the hands of the teachers from the basic education, the app will contribute to the popularization of the constructive knowledge, through the dissertations already presented, besides of propose to be a tool that enables the inclusion of other materials with the posterior access facilitated, without the need of internet, once installed. The methodology of this research was developed through of the following steps 1. Collection of data about the educational products that already have been produced; 2. Cataloguing of the Educational Products of the period between 2012 to 2015; 3. Development of the app; 4. Construction of the installation guide; 5. Moment of reflection in the Room Educator; 6. Construction and application of two questionnaires: It was applied to the teachers from the Public School Liceu Cuiabano/Cuiabá - MT; 7. Validation of the APP; The collection of data demonstrated that of the 26 available educational products in the Master Programs Database, 24 are compatible to the app and, therefore ,these products can be available to the teachers use it through the app. The characterization and cataloguing of each one of these products did expand the potential of access, due to the organization of each product in different areas, in a systematic way. The reflections in the Room Educator demonstrated a lot of difficult in relation of the use of the technologies. New apps are already being thinking based on this app, showing that the creative motivation for the science teaching affects continuing education by means of a professional master's and after it also. Based on the conclusions of the operational phases of this research, we proceed the final elaboration of the app, which will it be released and available to the teachers of the basic education and to the Master's Program, as well the Center of Centre for Training and Upgrading of basic education Professionals (Cefapro / Cuiaba-MT), the Teacher Portal and in the Play Store.